Оптимізація бізнес-процесів у готельно-ресторанному підприємстві як чинник підвищення якості сервісу та фінансових результатів діяльності - Побережна, Наталія Миколаївна; Куниця, Катерина Вікторівна; Стригуль, Лариса Станіславівна (Видавничий дім "Гельветика", 2025)
У статті досліджено питання оптимізації бізнес-процесів у готельно-ресторанному підприємстві як чинника підвищення якості сервісу та фінансових результатів діяльності. Обґрунтовано роль оптимізації та реінжинірингу бізнес-процесів готельно-ресторанного підприємства у забезпеченні стабільної якості сервісу, скороченні операційних витрат і підвищенні ефективності використання ресурсів. Доведено доцільність інтегрованого застосування сучасних управлінських підходів (BPM, Lean Management, Six Sigma, Agile, Kaizen) та визначено значення цифрової трансформації бізнес-процесів як інструменту автоматизації, підвищення прозорості управління і персоналізації сервісу. Практичне значення дослідження полягає у можливості його використання в оптимізації бізнес-процесів з метою підвищення якості послуг, ефективності роботи, конкурентоспроможності та фінансової стійкості.

The relevance of the research is determined by increasing competition in the hospitality industry, growing consumer requirements for service quality, and the need to improve the financial performance of hotel and restaurant enterprises in the context of economic digitalisation. In modern conditions, the efficiency of enterprise functioning is largely determined by the level of organisation of business processes, which directly affects service quality, customer satisfaction, and enterprise competitiveness. The purpose of the article is to study the optimisation of business processes of a hotel and restaurant enterprise as a factor in improving service quality and financial performance. The methodological basis of the research includes methods of analysis and synthesis, system and process approaches, comparative analysis, generalisation of scientific sources, as well as logical and structural analysis. The essence of business processes is considered with their classification according to the “performance criterion” and taking into account the specifics of service activities. The implementation of business process reengineering in a hotel and restaurant enterprise is proposed, covering the preparatory stage, diagnostics, redesign, and deployment of processes. The role of business process optimisation and reengineering in ensuring stable service quality, reducing operating costs, increasing labour productivity, and improving resource efficiency is substantiated. The expediency of the integrated application of modern management approaches to business process optimisation, including Business Process Management, Lean Management, Six Sigma, Agile, and Kaizen, taking into account the specifics of the hotel and restaurant business, is proved. The impact of management approaches on service quality and financial performance indicators is established. The importance of digital transformation of business processes as a tool for automation, increasing management transparency, and service personalisation is determined. The practical value of the article lies in the possibility of applying the obtained results and proposed recommendations in the activities of hotel and restaurant enterprises in order to improve operational efficiency, enhance corporate image, increase competitiveness, and strengthen financial sustainability.
Optimization of business processes in a hotel and restaurant enterprise as a factor of improving service quality and financial performance
Keywords: готельно-ресторанне підприємство; бізнес-процеси; реінжиніринг; цифрова трансформація; якість сервісу; фінансові результати; hotel and restaurant enterprise; business processes; reengineering; digital transformation; service quality; financial performance